Training for the Randu Alas Batik Group in Processing Batik Waste by Internet of Things - Sabila, Liya Yusrina; Amelia, Shinta; Subrata, Arsyad Cahya; Ma'arief, Sandhy Auliya; Fadhilla, Irvanda Cheza Noor; Yasa, Fakhra Kurnia (Indonesia Berdaya, 2024)
The Industrial Revolution 4.0 era has encouraged the integration of Internet of Things (IoT) technology in various sectors, including industrial waste management. This article discusses the implementation of IoT technology for processing batik liquid waste in the Randu Alas Batik Community Group, Mrisi, Tirtonirmolo, Bantul Regency, Yogyakarta. Batik liquid waste, which comes from the processing and dyeing process, contains dangerous chemicals that can increase chemical oxygen demand (COD) values and cause water pollution. This community service activity is carried out through outreach, training, and practice in using IoT-based waste processing equipment, which aims to increase community knowledge and skills in managing waste effectively and sustainably. The evaluation results show a significant increase in understanding and application of IoT, reflected in the pretest and post-test results. The conclusion of this activity shows that IoT technology effectively improves the quality of batik waste management and has great potential to be widely applied to maintain environmental sustainability.